Chronic Illness and Disability: Narratives of Suffering and Healing in Buddhism and Christianity - Schumm, Darla Y. (Journal of religion, disability & health, 2007)
In this paper we describe some of the unique personal, medical, social, and religious challenges facing people living with chronic illness and disability. Our specific focus involves the connections between suffering, healing, and disability in two religious traditions: Buddhism and Christianity. Two core questions focus our inquiry. First, why are chronic illness and disability often associated with merited suffering in Buddhism and Christianity? Second, what types of Buddhist and Christian practice can help cultivate spiritual healing in the midst of chronic conditions?